UNDERSTANDING OF THE LINTANG TRIBE SOCIETY ABOUT WOMEN WHO ARE HARAM TO BE MARRIED ON ISLAMIC LAW PERSPECTIVE - Zurifah Nurdin (AGENDA: Jurnal Analisis Gender dan Agama, 2021)
The Lintang tribal people who are predominantly embracing Islam, with a patrilineal family system, have a different understanding of women who are forbidden to marry, therefore this paper reveals the understanding of the Intang tribe community about women who are haram to marry from the perspective of Islamic law. In terms of description, the writer finds that the understanding of the Lintang tribe about women who are haram to marry is in line with the maqashid syri'ah, namely in order to maintain the safety of religion, reason and safety of soul even though there are differences from those in the books of fiqh. The indication of maintaining the three matters of maqashid syari'ah is maintaining the marriage guardian order, maintaining the offspring to be physically and mentally healthy, intelligent both socially and spiritually and not physically or mentally defective. Therefore the understanding as found in the Lintang Tribe community needs to be preserved because it is part of the Islam of the Archipelago